If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3(5x + -15) = 113 Reorder the terms: 3x + 3(-15 + 5x) = 113 3x + (-15 * 3 + 5x * 3) = 113 3x + (-45 + 15x) = 113 Reorder the terms: -45 + 3x + 15x = 113 Combine like terms: 3x + 15x = 18x -45 + 18x = 113 Solving -45 + 18x = 113 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + 18x = 113 + 45 Combine like terms: -45 + 45 = 0 0 + 18x = 113 + 45 18x = 113 + 45 Combine like terms: 113 + 45 = 158 18x = 158 Divide each side by '18'. x = 8.777777778 Simplifying x = 8.777777778
| -4(5p+3)-48=2(2p+6) | | 9(11-k)=3(3-9) | | 15=3-x+4 | | 45+20m=30+25m | | 0.66=1.33+6x | | -7x+3=7 | | 8d-4=12 | | 0.050x^2-x+1=0 | | -18-x=-17 | | V-x-y+z=4 | | 4x=21+sqrt(56-x) | | 6x+2(5x-18)=56 | | 7z+2=23 | | 1000+100w=5000 | | D+00.2d=510 | | 15x^2+7=0 | | (2x+5)*(4x-3)=0 | | 24+4x=4x | | 10000+100w=5000 | | b=b^2 | | 2x-49=17 | | 2c^2=-3c | | 4(T-5)+2=-9+c+5 | | 2x+6=-38 | | x^2+x^2-14x-49=169 | | 6x+7(-2x-17)=-175 | | 13x^2+39x=0 | | 3(j-6)=j+10 | | (2x+8)(2x+7)= | | 3q^2-6q=0 | | 20+5x=55 | | cox(2x)-9=0 |